Hippocampal damage in sepsis induced by lipopolysaccharide: The neuroprotective effects of pregabalin in a rat model (Annals of Medical Research, 2022)
Aim: An excessive immune response to bacterial infections can lead to sepsis, a condition with a high mortality rate. Lipopolysaccharide (LPS)-induced inflammation and oxidative stress cause hippocampal injury. We aimed to investigate the antioxidant, anti-inflammatory and neurogenic effects of pregabalin (PG) against hippocampal injury induced by LPS.Material and Methods: Twenty-four rats were divided into three different groups (Control, LPS (5 mg/kg), and LPS+PG (30 mg/kg)). Six hours after LPS administration, animals were sacrificed, and the hippocampus tissue was gathered for biochemical, histopathological, and immunohistochemical research.Results: Biochemical and immunohistochemical analyses revealed the increased levels of total oxidant status (TOS), oxidative stress index (OSI), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β) and decreased expressions of total antioxidant status (TAS), brain-derived neurotrophic factor (BDNF), and sirtuin-1 (SIRT-1) in LPS group. In addition, histopathological analyses detected degenerative neurons, hyperemia, and edema.Conclusion: PG treatment reversed biochemical and immunohistochemical parameters and improved hyperemia, edema, and degenerative changes. In conclusion, PG increased BDNF and SIRT-1 levels by inhibiting inflammation and oxidative stress.
Keywords: BDNF; hippocampus; pregabalin; sepsis; SIRT-1